IDENTIFIKASI KESULITAN BELAJAR SISWA SAAT PEMBELAJARAN DI KELAS KELAS VI MI WAISELANG - Amaludin, La; Awal, Rawia (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Abstract Background: Student learning difficulties are a condition where students cannot learn normally, due to threats, obstacles or disruptions in learning. Methods: This research is a descriptive study which aims to determine students' learning difficulties in class VI MI Waiselang. This research uses a survey where related parties are asked to fill out several questionnaires regarding their experiences conducting online learning during the Covid-19 pandemic. Data analysis uses Likert scale analysis techniques. The instruments used in this research were questionnaires and interviews. Results: The results of the research show that the maximum respondent score is 30, so a presentation worth 3.00% is obtained, students with a maximum respondent score is 1,935, then a presentation worth 1.71% is obtained. Conclusion: The research interval data is a score of 0-19.99 with 8 frequencies with strongly disagree criteria, then a score of 60-79.99 with 1 frequency with agree criteria.